The Future of China’s Development and Globalization. By Henry H. Wang and Mabel L. Miao. Springer 2024 - CARSON, Scatt (Journal of Economics Library, 2025)
The Future of China’s Development and Globalization is an insightful collection of essays and candid discussions from various ambassadors posted in Beijing, published by the Center for China and Globalization (CCG). The volume addresses the shifting global landscape marked by post-pandemic recovery, increasing geopolitical tensions, and the growing influence of the Global South. The book’s central purpose is to provide an essential diplomatic perspective on China’s current state and its evolving role in the global order. It is divided into three main parts: examining the historical and current state of China’s diplomatic relations with various countries (e.g., Pakistan, Croatia, Switzerland, Sri Lanka, Spain, and the EU) , focusing on specific areas of potential cooperation such as economic governance and digital transformation , and discussing the future of global development in which China plays an essential role. The collected views underscore the necessity of maintaining open communication channels, fostering multilateralism, and ensuring China and major global powers collaborate on transnational challenges like global governance, climate change, and technology. Keywords. China-Global Relations; Global Governance; Multilateralism; Chinese Development; Diplomatic Perspectives. JEL. F50; O53; F02; F13; P16.